The Power of "Open". Issue 1 (1st May 2017) - Joseph, Heather; Davis, Susan
ABSTRACT: In a vision session at the 31st NASIG Annual Conference, Heather Joseph provided an assessment of the Open Access movement addressing how far it has come since its inception, how well it has met its original goals, what has and has not worked well, and what is not happening at all. She talked about the importance of open (in all senses—open access, open education, and open data) as a public good, and shared feedback from a recent strategic review of the Scholarly Publishing and Academic Resources Coalition and the Open Access movement. Joseph also explored the implications of using open as an enabling strategy for researchers, scholarly publishers, policymakers, and the larger academic community, and emphasized the importance of deliberately considering what outcomes open can help each community achieve—rather than thinking about open as an end to itself.